Research of Adding Parking Brake in CRH2 EMUs - SU Chao; GAO Qi (机车电传动)
According to the characteristics of parking brake and CRH2 EMUs brake system, a design scheme and pipe gram and electric control circuits used for parking brake in CRH2 was proposed , and the theoretical calculation was done. The proposed parking brake module perfect function structure is matched well with the brake system in CRH2 EMUs.